Deepak Scored 45->99%ile with Bounce Back Crack Course. You can do it too!

If f(x)

Question:

If f(x) = x2 − 3x + 4, then find the values of x satisfying the equation f(x) = f(2x + 1).

Solution:

Given:

f (x) = x2 – 3x + 4

Therefore,

(2x + 1) = (2x + 1)– 3(2x + 1) + 4

= 4x2 + 1 + 4x – 6x – 3 + 4

= 4x2 – 2x + 2

Now,
(x) = f (2x + 1)

⇒ x2 – 3x + 4 = 4x2 – 2x + 2

⇒ 4x2 – x2 – 2x + 3x + 2 – 4 = 0

⇒ 3x2 + x – 2 = 0

⇒ 3x2 + 3x – 2x – 2 = 0

⇒ 3x(x + 1) – 2(x +1) = 0

⇒ (3x – 2)(x +1) = 0

⇒ (x + 1) = 0  or  ( 3x – 2) = 0

$\Rightarrow x=-1$ or $x=\frac{2}{3}$                

Hence, $x=-1, \frac{2}{3}$.

 

Leave a comment

None
Free Study Material